MR protocol optimization for hepatobiliary phase imaging with Gd-EOB-DTPA at 1.5 T: comparison between breath-hold T1-weighted and high-resolution navigated 3D T1-weighted sequences - Eliseo Picchi; Valentina Ferrazzoli; Valeria Liberto; Luca Toti; Valerio Da Ros; Noemi Pucci; Silvia Minosse; Francesco Garaci; Francesca Di Giuliano (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background This study aims to compare the efficacy of navigator-gated three-dimensional T1-weighted gradient-echo sequences (NAV) with standard breath-hold T1-weighted gradient-echo sequences (BH) for the detection of hepatocellular carcinoma (HCC) nodules in patients with chronic viral hepatitis undergoing magnetic resonance imaging (MRI) with gadolinium ethoxybenzyl-diethylenetriaminepentaacetic acid (Gd-EOB-DTPA). Methods From May 2022 to November 2023, fifty-eight patients were included in this retrospective study. Eligible patients had chronic viral hepatitis and at least one hepatic nodule of one cm or larger detected by ultrasound. Each patients underwent MRI that included NAV and BH sequences obtained by using various flip angles (FA) ranging from 10° to 40° post Gd-EOB-DTPA administration. Three independent radiologists performed qualitative analysis evaluating the clearness of the image, the presence of artifacts, the diagnostic reliability of the sequences, and the contrast-to-noise ratio (CNR) between lesions and liver, as well as between liver and spleen. Results NAV sequences at a FA of 40° have demonstrated the highest agreement across all quality parameters (p < 0.001). A comparison of CNR between hypointense lesions and liver tissue showed decreasing values with increase FA, notably in NAV sequences. Statistically significant differences were observed among the sequences: BH 10° 0.73 ± 0.17; BH 30° 0.68 ± 0.17; BH 40° 0.68 ± 0.15; NAV 25° 0.62 ± 0.18; NAV 40° 0.56 ± 0.17. Although sequences with higher FA have shown an increase in CNR and contrast between liver and spleen, no statistically significant differences have been detected between BH and NAV with 40° of FA. Conclusions The study highlighted the diagnostic superiority of NAV over BH sequences with a 40° FA in assessing image quality and enhancement in malignant liver nodules of cirrhotic patients. Incorporating one of these sequences into MRI protocols is recommended for enhanced diagnostic clarity, which is critical for informed surgical planning. This could facilitate more precise interventions, potentially improving surgical outcomes in the management of hepatocellular carcinoma.